The three little fish and the big bad shark - Geist, Ken (New York : Cartwhell books, 2007)
In this spoof of the three little fish, Mama tells her three little fish that it's time to seek their fortunes. Jim builds a houseof seaweed and tim builds a house of sand, but it's up to kim to find the house that will stop the big bad shark's munching and crunching.
Keywords: Fishes -- Juvenile literature; Sharks -- Juvenile literature